Implementasi Pengaturan Kelembaban Tanah Pembumian Berbasis Mikrokontroler Arduino - Hikmatul Amri; Jefri Lianda (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2018)
In the measurement of the grounding resistance in an installation is strongly influenced by the type of soil in which the grounding electrode is planted, soil layer, soil moisture and temperature. In the measurement of the grounding resistance the condition of an electrical installation shall have an grounding resistance less than or equal to 5Ω. To obtain accurate grounding resistivity measurement results, the application of digital system is required. In this research is the implementation of the reading system, monitoring the grounding resistance and maintaining the soil moisture level on the electrode rod so that the maximum 5Ω grounding resistance threshold can be maintained. The purpose of this system is to monitor the value of grounding resistance in the building area and to maintain soil moisture level for the grounding resistance under ideal conditions. The system can read the grounding resistance by obtaining information from the voltage and current sensors, displaying data on the LCD and maintaining the soil moisture by controlling the selenoid valve water that regulates the flow of water from the tank to the ground implanted rod electrode. From the research that has been done, the result of the error of reading of grounding resistance is 2,40% when compared to meeger measuring instrument, and controller response in regulating selenoid valve water if grounding resistance rises above 5Ω because dry soil has 100% success.